Fundamentals of Jewish conflict resolution : traditional Jewish perspectives on resolving interpersonal conflicts - Kaminsky, Howard, 1960- (Studies in Orthodox Judaism, 2017)
"Fundamentals of Jewish Conflict Resolution offers an in-depth presentation of traditional Jewish approaches to interpersonal conflict resolution. It examines the underlying principles, prescriptive rules, and guidelines that are found in the Jewish tradition for the prevention, amelioration, and resolution of interpersonal conflicts, without the assistance of any type of third-party intermediary. Among the topics discussed are the obligations of pursuing peace and refraining from destructive conflict, Rabbinic perspectives on what constitutes constructive/destructive conflict, judging people favorably and countering negative judgmental biases, resolving conflict through dialogue, asking and granting forgiveness, and anger management. This work also includes detailed summaries of contemporary approaches to interpersonal conflict resolution, theories and research on apologies and forgiveness, and methods of anger management"--